PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK MULIA PESERTA DIDIK DI MADRASAH ALIYAH MAMBAUL ULUM POWAK - Rofi’i Rofi’i (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study examines the professionalism of Islamic Religious Education teachers in fostering the noble character of students at Madrasah Aliyah Mambaul Ulum Powak Pamekasan. This research is a qualitative research using a phenomenological research approach. The research instrument is the researcher himself. Sampling technique and purposive sampling and snowball sampling. Using data collection in the field using observation, interviews, and documentation techniques, as well as sources of research data are school principals, Islamic education teachers and extracurricular teachers, vice principals, students, and other information deemed necessary in collecting this research data. This study explains that the professionalism of Islamic Religious Education teachers at Madrasah Aliyah Mambaul Ulum Powak Pamekasan is quite contributing to the formation of noble character of students, especially in the school environment. The description of the noble character of students at Madrasah Aliyah Mambaul Ulum Powak Pamekasan when viewed from the aspect of discipline in participating in school activities, harmony between students, characteristics in worship, and mutual assistance and responsibility in carrying out tasks assigned by the teacher, has been able to be actualized in the school environment although most of them still seem just a mere formality. Professional efforts made by Islamic Religious Education teachers in fostering the noble character of students at Madrasah Aliyah Mambaul Ulum Powak Pamekasan are making daily, weekly, and annual programs. Penelitian ini mengkaji profesionalisme guru Pendidikan Agama Islam dalam pembinaan akhlak mulia peserta didik di Madrasah Aliyah Mambaul Ulum Powak Pamekasan. Penelitian ini adalah penelitian kualitatif dengan menggunakan pendekatan penelitian fenomenologi. Intrumen penelitian adalah peneliti sendiri. Teknik sampling dan  purposive sampling dan snowball sampling. Menggunakan pengumpulan data di lapangan dengan menggunakan teknik observasi, wawancara, dan dokumentasi, serta Sumber data penelitian ialah kepala sekolah, guru pendidikan islam dan Guru exstrakurekuler, wakil kepala sekolah, peserta didik, dan informasi lainnya yang dianggap perlu dalam pengumpulan data penelitian ini.Hasil penelitian ini menerangkan bahwa profesionalisme guru Pendidikan Agama Islam di Madrasah Aliyah Mambaul Ulum Powak Pamekasan cukup berkontributif terhadap pembentukan akhlak mulia peserta didik khususnya di lingkungan sekolah. Adapun gambaran akhlak mulia peserta didik di Madrasah Aliyah Mambaul Ulum Powak Pamekasan apabila ditinjau dari aspek kedisipilinannya dalam mengikuti kegiatan di sekolah, kerukunan antar peserta didik, keistikomaan dalam melakukan ibadah, dan tolong-menolong serta tanggung jawab dalam melakukan tugas yang diberikan oleh guru, sudah mampu diaktualisasikan di dalam lingkungan sekolah walaupun sebagian besar masih terkesan sekadar formalitas belaka. Upaya profesional yang dilakukan oleh guru Pendidikan Agama Islam dalam membina akhlak mulia peserta didik di Madrasah Aliyah Mambaul Ulum Powak Pamekasan yaitu membuat program harian, mingguan, dan tahunan.